EVALUASI MASTITIS SUBKLINIS PADA SAPI PERAH DI PETERNAKAN RAKYAT KAPUPATEN TANGGAMUS MENGGUNAKAN UJI MASTITIS DAN JUMLAH SEL SOMATIK - Dian Cahya Hadi; Veronica Wanniatie; Arif Qisthon; Purnama Edy Santosa (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study aimed to determine the presence or absence of subclinical mastitis cases with mastitis test IPB-1 and somatic cell count calculation of the Breed method for dairy milk farm in Tanggamus Regency. The study was conducted in January 2020. Milk specimens were taken from farmers in Gisting Atas and Air Naningan district areas of Tanggamus Regency, Lampung Province. Specimen testing was carried out at the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Specimens of milk used were obtained from farms in the Gisting Atas region as many as 9 lactation dairy cows and 10 lactation dairy cows from farms in the Air Naningan region. This research method was a survey by taking farm data through interviews, taking milk specimens for mastitis testing with the reagents of IPB-1, taking specimens to be used as preparations which are then tested to somatic cell count using the breed method. The variables observed were the results of mastitis test and the results of somatic cell counts in dairy milk. Data were processed in tabulation and histogram then explained descriptively. The mastitis test results showed that 33% of cow nipples from Gisting Atas farms and 37% of nipples from Air Naningan farms positively had subclinical mastitis. Calculation of the number of somatic cells showed that the average number of somatic cells was 2,341,538 cells / ml for the Gisting Atas area and as much as 821,176 cells / ml for the Air Naningan region. Keywords: Subclinical mastitis, IPB-1 test, Breed method, Somatic cells, dairy milk